Art 1971 The Role of Religiosity in Moderating the Influence of Materialism, Repayment Capacity, and Economic Conditions on Financing Quality - Maura Faradita; Aqwa Naser Daulay; Isnaini Harahap (IAI Ummul Ayman, Meureudu, Pidie Jaya, Aceh, Indonesia, 2026)
This study aims to analyze the influence of materialism, repayment capacity, and economic conditions on financing quality, as well as to test the role of religiosity as a moderating variable. This study uses a quantitative approach with data obtained through direct questionnaire distribution by researchers to respondents. The data collection technique used Purposive Sampling technique with the target respondents being BSI KCP Pangkalan Brandan financing customers. The analysis technique used is Moderated Regression Analysis (MRA). The results of the study indicate that materialism partially has a negative and significant effect on financing quality, while repayment capacity and economic conditions partially have a significant positive effect. The influence of materialism, repayment capacity, and economic conditions simultaneously also affect financing quality. Furthermore, the results of the moderation test indicate that religiosity is able to moderate the relationship between materialism,repayment capacity, and economic conditions on financing quality. Religiosity is proven to weaken the negative influence of materialism and strengthen the positive influence of repayment capacity and economic conditions. The results of this study provide a more comprehensive understanding to the public while enriching insight regarding various factors that influence financing quality, especially in Islamic banking such as Bank BSI KCP Pangkalan Brandan. This research fills this gap by examining how religiosity plays a role in strengthening or weakening the influence of these three variables on financing quality, thus providing a new, more holistic and relevant perspective for managing financing based on Sharia values.